Tecendo saberes, articulando alianças: um estudo sobre a subjetividade contemporânea a partir das contribuições de Adorno e de Guattari - Xavier, Monalisa Pontes (2009)
The present work aims at developing a study of the contemporary subjectivation processes, departing from the influence of the capitalist system on them. For so, a theoretical articulation will be drawn among the writings of Theodor W. Adorno – frankfurtian theorist – and Félix Guattari- theorist and institutional analyst, who acts in several domains: psychiatry, anthropology and politics. Such thinkers based their studies on subjectivity, distinctive moments of the capitalist system of production and consumption. In such articulation, we take the concepts of “individualization” and “singularity” developed by Adorno and Guattari, respectively. Therewith, we aim, by opposing the ideas of the authors, to increase the understanding over the process of constitution of contemporary subjectivity, as well as to perceive the existence of “individual” and/or “singularized” existence. It was developed a theoretical research ruled in bibliographical review of the respective authors’ writings as well as of other speakers who made possible the enrichment of understanding concerning the object of study. To reach the proposed goal, we followed some steps: in the first chapter we exposed a possible intersection between Adorno and Guattari, departing from the philosophical tendency of the ontology of the present; in the following chapter, we discussed Adorno’s theory and the process of individuation; then we went through the Guatarri’s theory and the singularization movement; at last, we looked up articulations and tried to catch a glimpse into alliances between the two theorists. By the end of the research we emphasized the need to consider each of the theories in accordance with the Theoretical-Philosophical tradition to which it is affiliated. Therefore, it is made impossible a logical articulation among what the two of them have as important for the understanding of our object. Nevertheless, it is departing from the tension and contradiction existing among them that we can reach a better understanding concerning the processes of subjectivation in the present days, which is not that about which Adorno’s reflexions would be devoted to neither the same proclaimed by Guattari.